The Reform of China's Exchange Rate Regime - Luo, Xuefen (2006)
In July 2005 the Chinese government announced a switch to a new exchange rate regime. The new exchange rate regime is set with reference to a basket of currency. But the numerical weights of each currency in the basket are unannounced. Under economic and political pressures, China adjusted his exchange rate regime, which is no longer a peg to the US dollar. Subsequently, with the appreciation of the Chinese Yuan, China allowed a movement of the exchange rate up to 3% within any given day. Perhaps, the new exchange rate policy has an impact on the imports and exports, even other countries' exchange rate policy, the international imbalance and financial market. We argue that China is not really conducting the basket of currency policy after the reform. The Chinese government released the composition of basket currencies and the determinant of currency weights. But the exact weights are still unknown.